Diagnostic utility of LDH measurement for determining the etiology of modified transudate pleural effusion in cats - Mon Hla, Hsu; Hunprasit, Vachira; Siripoonsup, Jedsada; Rungsipipat, Anudep; Radtanakatikanon, Araya (Frontiers in Veterinary Science, 2022)
Fluid analysis is an initial approach for determining the underlying causes of body cavity effusions. Modified transudate is commonly diagnosed in pleural effusion in cats, however, it provides limited diagnostic information. Aims of this study were to investigate common etiologies causing different pleural fluid types and to evaluate the usefulness of lactate dehydrogenase (LDH) for differentiating the etiology in modified transudates in cats. Pleural effusion samples from 122 cats were analyzed and classified into 3 types: transudate, modified transudate and exudate. Causes of pleural effusion were classified into 4 conditions: cardiac disease, neoplasia, feline infectious peritonitis (FIP), and pyothorax. The relationship of underlying etiology and fluid types was described. The LDH levels in pleural fluid and plasma were compared between the causes in the samples classified as modified transudate. The fluid analysis of pleural effusion showed that modified transudate was the most common (44.2%) fluid type. Neoplasia was predominantly diagnosed (38.5%) as the etiology of pleural effusion. There was no significant correlation between pleural fluid and plasma LDH level in any type of pleural fluid suggested that pleural fluid LDH does not appear to be affected by plasma LDH. The occurrence of modified transudate was not associated to its etiologies however, the LDH level in modified transudates showed significant differences between etiologic groups. The LDH level in modified transudate was excellent at separating cardiac from non-cardiac diseases with a cut-off value of <535 U/L and separating FIP from non-FIP diseases with a cut-off value of >641 U/L. Based on the current findings, pleural fluid LDH can be a useful adjunctive marker for differentiating some causes of modified transudate pleural effusion and should be added in the routine diagnostic work-up of feline patients with pleural effusions.